A comparison of assays for accurate copy number measurement of the low-affinity fc gamma receptor genes FCGR3A and FCGR3B - Haridan, Umi Shakina; Mokhtar, Umairah; Machado, Lee R.; Abdul Aziz, Abu Thalhah; Shomiad @ Shueb, Rafidah Hanim; Zaid, Masliza; Sim, Benedict; Mustafa, Mahiran; Nik Yusof, Nik Khairudin; Lee, Christopher K. C.; Abu Bakar, Suhaili; Abu Bakar, Sazaly; et al. (Public Library of Science, 2015)

(untitled)
The FCGR3 locus encoding the low affinity activating receptor FcγRIII, plays a vital role in immunity triggered by cellular effector and regulatory functions. Copy number of the genes FCGR3A and FCGR3B has previously been reported to affect susceptibility to several autoimmune diseases and chronic inflammatory conditions. However, such genetic association studies often yield inconsistent results; hence require assays that are robust with low error rate. We investigated the accuracy and efficiency in estimating FCGR3 CNV by comparing Sequenom MassARRAY and paralogue ratio test-restriction enzyme digest variant ratio (PRT-REDVR). In addition, since many genetic association studies of FCGR3B CNV were carried out using real-time quantitative PCR, we have also included the evaluation of that method's performance in estimating the multi-allelic CNV of FCGR3B. The qPCR assay exhibited a considerably broader distribution of signal intensity, potentially introducing error in estimation of copy number and higher false positive rates. Both Sequenom and PRT-REDVR showed lesser systematic bias, but Sequenom skewed towards copy number normal (CN = 2). The discrepancy between Sequenom and PRT-REDVR might be attributed either to batch effects noise in individual measurements. Our study suggests that PRT-REDVR is more robust and accurate in genotyping the CNV of FCGR3, but highlights the needs of multiple independent assays for extensive validation when performing a genetic association study with multi-allelic CNVs.